Iteration process for multiple Rogers-Ramanujan identities - Chu, W.; Wang, C. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Replacing the monomials by an arbitrary sequence in the recursive lemma found by Bressoud (1983), we establish several general transformation formulas from unilateral multiple basic hypergeometric series to bilateral univariate ones, which are then used for the derivation of numerous multiple series identities of Rogers-Ramanujan type.